Funding structure and profitability as moderating variables strengthen the impact of eco-efficiency on firm value - Wardany, Indah; Ranitawati, Endang; Yahya, Yahya (Implementasi Manajemen & Kewirausahaan, 2024)
The aim of this research is to empirically test the impact of eco-efficiency on company value which is strengthened by the mediation of funding structure and profitability. Where eco-efficiency is proxied by the ISO 140001 certificate, company value is measured by the TOBINS'Q ratio, funding structure is measured by leverage, and for profitability it is proxied by return on assets (ROA). Testing this research uses Moderate Regression Analysis (MRA) with secondary data from a sample of 225 manufacturing companies in various industrial sectors listed on the IDX for the period 2028 - 2022. The results of this research show that the effect of eco-efficiency on company value is negatively significant, while for the media variable has a significant positive effect in strengthening the influence of eco-efficiency in company value. Keywords : eco-efficiency, funding structure, profitability, company value